Palladium‐Catalyzed Suzuki–Miyaura Coupling Reactions of Boronic Acid Derivatives with Aryl Chlorides. Issue 10 (16th August 2016) - Zhou, Zihong; Zhang, Yaqi; Xia, Wang; Chen, Huixuan; Liang, Hao; He, Xuefeng; Yu, Sifan; Cao, Rihui; Qiu, Liqin
Abstract: A series of new biphenyl N, P‐monophosphine ligandsL have been developed by introduction of two methoxy groups to the biphenyl backbone. The ligands were found to be much more effective than their counterpart Buchwald ligands in Suzuki–Miyaura coupling reactions of sterically hindered and electron‐rich aryl chlorides with aryl boronic acids. A variety of tri‐ ortho ‐substituted or tetra‐ ortho ‐substituted biaryls or hetero‐biaryls were conveniently prepared in up to 99 % yield by usingL1 ‐[Pd2 (dba)3 ] (dba=dibenzylideneacetone) as the catalyst. Abstract : Improved coupling reactions : A series of new biphenyl N, P‐monophosphine ligandsL have been developed by introduction of two methoxy groups to the biphenyl backbone. The ligands were found to be much more effective than their counterpart Buchwald ligands in Suzuki–Miyaura coupling reactions of sterically hindered and electron‐rich aryl chlorides with aryl boronic acids. A variety of tri‐ ortho ‐substituted or tetra‐ ortho ‐substituted biaryls or hetero‐biaryls were conveniently prepared in up to 99 % yield by usingL1 ‐[Pd2 (dba)3 ] (dba=dibenzylideneacetone) as the catalyst.